Incidence of Primary Mitochondrial Disease in Children Younger Than 2 Years Presenting With Acute Liver Failure. Issue 6 (December 2016) - McKiernan, Patrick; Ball, Sarah; Santra, Saikat; Foster, Katherine; Fratter, Carl; Poulton, Joanna; Craig, Kate; McFarland, Robert; Rahman, Shamima; Hargreaves, Iain; Gupte, Girish; Sharif, Khalid; et al.
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Background: Mitochondrial liver disease (MLD), and in particular mitochondrial DNA (mtDNA) depletion syndrome (MDS) is an important cause of acute liver failure (ALF) in infancy. Early and accurate diagnosis is important because liver transplantation (LT) is often contraindicated. It is unclear which methods are the best to diagnose MLD in the setting of ALF. Objective: The aim of the study was to determine the incidence of MLD in children younger than 2 years with ALF and the utility of routine investigations to detect MLD. Methods: Thirty-nine consecutive infants with ALF were admitted to a single unit from 2009 to 2011. All were extensively investigated using an established protocol. Genes implicated in mitochondrial DNA depletion syndrome were sequenced in all cases and tissue mtDNA copy number measured where available. Results: Five infants (17%) had genetically proven MLD: DGUOK (n = 2), POLG (n = 2), and MPV17 (1). Four of these died, whereas 1 recovered. Two had normal muscle mtDNA copy number and 3 had normal muscle respiratory chain enzymes. An additional 8 children had low hepatic mtDNA copy number but pathogenic mutations were not detected. One of these developed fatal multisystemic disease after LT, whereas 5 who survived remain well without evidence of multisystemic disease up to 6 years later. Magnetic resonance spectroscopy did not distinguish between those with and without MLD. Conclusions: Low liver mtDNA copy number may be a secondary phenomenon in ALF. Screening for mtDNA maintenance gene mutations may be the most efficient way to confirm MLD in ALF in the first 2 years of life.